Geraniin induces apoptosis of human breast cancer cells MCF-7 via ROS-mediated stimulation of p38 MAPK. (12th June 2016) - Zhai, Jia-Wen; Gao, Chang; Ma, Wei-Dong; Wang, Wei; Yao, Li-Ping; Xia, Xin-Xin; Luo, Meng; Zu, Yuan-Gang; Fu, Yu-Jie
Abstract: Geraniin, a typical ellagitannin isolated from Phyllanthus urinaria Linn, has been found to possess a range of bioactive properties. In the present study, we found that Geraniin showed potent anti-proliferative effects on human breast cancer MCF-7 cells. The IC50 values were 9.94, 17.98 and 42.32 µM after 72-, 48- and 24-h treatment, respectively. Meanwhile, Geraniin could remarkably disrupt mitochondrial membrane potential and arrest S phase cell cycle. Western-blot analysis showed that Geraniin induced phosphorylation of the anti-apoptotic Bcl-2, and the cleavage of poly (ADP-ribose) polymerase (PARP) and caspase-3 in MCF-7 cells. Moreover, Geraniin treatment activated p38 mitogen-activated protein kinase (p38 MAPK) and the effect was blunted in MCF-7 cells with the treatment of a specific p38 inhibitor SB203580. Geraniin could generate intracellular reactive oxygen species (ROS), activate p38 MAPK then induce the apoptosis in MCF-7 cells, such phenomena was abrogated by pretreatment with N -acetyl-l -cysteine. In general, these results support the conclusion that Geraniin-induced apoptosis is mediated via ROS-mediated stimulation of p38 MAPK signaling.